Exploring model chemical systems through a new lens: combining novel microfluidic technology with infrared analysis techniques - Barich, Michael, author; Krummel, Amber T., advisor; Levinger, Nancy, committee member; Strauss, Steve, committee member; Kipper, Matt, committee member; Bartels, Randy, committee member (Colorado State University. Libraries, 2016)
Multiple designer peptides, such as RADA-16, have been used as model systems to investigate the chemical parameters that influence protein folding and self-assembly processes. As such, the cause and effect relationship between folding outcomes and folding environmental factors have been extensively investigated. However, the mechanism of the folding process is largely unexplained due to the lack of an analysis technique that can capture structural changes on the time scale of the folding process. This thesis is the first step towards the ability to monitor the protein folding process with atomic structural resolution in real time. In this work, the sample handling capabilities of microfluidic devices are used to expand the experimental range of both infrared (IR) and two dimensional infrared (2D IR) measurement techniques. This includes the development of novel channel designs, overcoming IR compatibility issues, and setting precedent in monitoring chemical processes within microfluidic devices. Microfluidic channel geometries that perform microsecond mixing were developed to allow access to early reaction kinetics. A novel fabrication technique was developed to afford IR analysis methods to be utilized in microfluidic detection schemes. Lastly, model chemical reactions were studied in both Fourier transform IR microspectroscopy (FTIR microspectroscopy) and 2D IR spectroscopy experiments to highlight the applicability of the technology towards a broad range of chemical and biological systems, including the protein folding and self assembly processes.
Keywords: microfluidic; spectroscopy; protein folding; infrared